Historia interpretacji Nowego Testamentu - Langkammer, Hugolin (The Biblical Annals, 2017)
The paper deals with a history of the interpretations of the texts of the New Testament. It tells us about their creation and development as well as presents the results of this process. The first part reveals subsequent stages of the practical application of the exegesis (and even traces of there being some comments in the NT as to earlier tradition) from the post-apostolic time until the Middle Ages. The second, however, concentrates on the stages of the development of a scientific interpretation of the NT’s text, taking into account the factors which stimulated it. This part spans over the period from humanism until Vatican Council II and also takes into account the repercussions which its teaching has brought about.